Pengaruh Pijat Oksitosin dan Totok Payudara terhadap Pengeluaran Asi pada Ibu Nifas: The Effects of Oxytocin Massage and Breast Acupressure on the Expenditure of Breast Milk among Postpartum - Widya Pani; Sri Restu Tempali (Jurnal Bidan Cerdas, 2022)
Introduction: Breast milk is a good source of nutrients. Breast milk is given to babies from birth for six months, without adding and/or replacing with other foods or drinks. Breast milk contains colostrum which is rich in antibodies because it contains protein for the immune system and high amounts of germ killer so that exclusive breastfeeding can reduce the risk of death in infants. Purpose This study aims to determine the effect of oxytocin massage and breast acupuncture on the release of breast milk in postpartum mothers in the postpartum room at Donggala and Sigi Regency Hospitals. Method Type This research is a type of pre-experimental research with a one shot case study research design. The sample was determined using the Sample Proportion Estimation Formula with a result of 15. The sample was divided into two groups, so that the total number of samples was 30 samples, namely 15 for the Oxytocin Massage group and 15 for Full-blooded Breasts. Sampling was carried out using the Consecutive Sampling technique. Every postpartum mother who met the inclusion criteria were normal postpartum mothers with a history of 37-42 weeks of pregnancy, normal postpartum mothers without complications, second and third day postpartum mothers. Results Nonpatrametric test results Bivariate analysis using t-test with a sample of 30 postpartum mothers, it was found that 30 respondents all experienced breast milk expulsion after a full-blooded breast intervention. The p-value = 0.000 which means it is smaller than = 0.05 (0.000 < 0.05) that there is an effect of Oxytocin massage and full-blooded breasts on breastfeeding mothers in postpartum. The conclusion is that there is an effect of oxytocin massage and breast acupuncture on milk production at Kabelota Donggala Hospital and Torabelo Sigi Hospital Conclusion: There is an effect of oxytocin massage and breast acupuncture on the release of postpartum mother's milk in the working area of ​​Kabelota Donggala Hospital and Torabelo Sigi Hospital.   ABSTRAK Pendahuluan: ASI merupakan sumber nutrizi yang baik. ASI diberikan kepada bayi sejak dilahirkan selama enam bulan, tanpa menambahkan dan/atau mengganti dengan makanan atau minuman lain. ASI mengandung kolostrum yang kaya akan antibodi karena mengandung protein untuk daya tahan tubuh dan pembunuh kuman dalam jumlah tinggi sehingga pemberian ASI eksklusif dapat mengurangi risiko kematian pada bayi. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh pijat oksitosin dan totok payudara terhadap pengeluaran ASI pada ibu nifas Di Ruangan Nifas Rumah Sakit Kabupaten Donggala Dan Kabupaten Sigi. Metode: Jenis Penelitian ini merupakan jenis penelitian pre eksperimental dengan rancangan penelitian one shot case study. Sampel di tentukan menggunakan Rumus Estimasi Proporsi sampel dengan hasil 15. Sampel dibagi menjadi dua kelompok, sehingga total jumlah sampel adalah 30 sampel yaitu 15 untuk kelompok Pijat Oksitosin  dan 15 untuk Totok Payudara. Pengambilan sampel dilakukan menggunakan teknik Consecutive Sampling. Setiap ibu postpartum yang memenuhi kriteria inklusi yaitu Ibu postpartum normal dengan riwayat kehamilan 37-42 minggu, Ibu postpartum normal tanpa penyulit, Ibu postpartum hari kedua dan ketiga. Hasil: Hasil uji Nonpatrametric Test analisis bivariat menggunakan uji t dengan jumlah sampel 30 responden ibu nifas diperoleh hasil 30 responden semua mengalami pengeluaran ASI setelah dilakukan intervensi totok payudara. Nila p-value=0,000 yang berarti lebih kecil dari α = 0,05 (0,000 < 0,05) bahwa ada pengaruh Pijat Oksitosi dan totok payudara terhadap pengeluaran ASI pada ibu nifas. Kesimpulan ada pengaruh pijat oksitosin dan totok payudara terhadap pengeluaran ASI Di RS Kabelota Donggala Dan RS Torabelo Sigi. Kesimpulan: Ada pengaruh pijat oksitosin dan totok payudara terhadap pengeluaran ASI ibu nifas di wilayah kerja Rumah Sakit Kabelota Donggala dan Rumah Sakit Torabelo Sigi.